La productividad y su incidencia en el desarrollo empresarial de la empresa Agua Mineral “San Felipe” . - Guamangate Gavilanez, Mery Alexandra (2024)
Productivity is an issue of great importance within organizations, as it plays a fundamental role in the success and efficiency of different companies or organizations in the long term, as it impacts their competitiveness and capacity to face the challenges of the market. On the other hand, business development is essential to drive a company's growth, innovation, and profitability and maintain its relevance and sustainability in a dynamic and competitive business environment. This research project aims to analyze the relationship between productivity and its impact on business development in the mineral water company "San Felipe," for which quantitative research was used through the collection and analysis of numerical data; in this area was collected information from the company, in order to know the relationship between the dependent and independent variable. Previously, using the Excel tool and SPSS 25 software, a high correlation between production, sales, and available capacity was determined. In this way, it was possible to analyze productivity and business development positively related through its indicators and dimensions.